EFFECT OF SOLVENT TYPE ON THE PHYTOCHEMICAL CONTENT AND THE SPECIFIC AND NON-SPECIFIC PARAMETERS OF JOMBANG (Taraxacum officinale) LEAF EXTRACTS - Syafriana, Vilya; Azzahra, Hudia Akmalia; Vasya, Zahra Ifany; Subaryanti, Subaryanti; Muti, Annisa Farida (BRIN Publishing (Penerbit BRIN), 2025)
Jombang (Taraxacum officinale) is a wild plant commonly used by the Javanese as a traditional medicine. This study aimed to perform phytochemical screening and analyze both specific and non-specific characteristics of Jombang leaf extracts obtained using four different solvents: ethyl acetate, 80% ethanol, 50% ethanol, and aqueous. Specific parameters included sample identity and organoleptic properties, while non-specific parameters covered drying loss, specific gravity, ash content, and water content. All tests refer to the Indonesian Materia Medika and the Indonesian Herbal Pharmacopeia as standards for medicinal plants. The phytochemical content of each extract varied, with tannins present in all four extracts. Flavonoids were not found in the 80% ethanol extract. Steroids were detected in both the ethyl acetate and aqueous extracts, while triterpenoids and alkaloids were present only in the ethanol extracts. Saponins were found in the 50% ethanol and aqueous extracts. Non-specific characteristics showed that the organic solvent extracts met the drying loss requirement of no more than 11%, whereas the aqueous extract exceeded this limit with a value of 13.72%. The specific gravity of the four extracts ranged between 0.04 and 0.10 g/mL, and the water content of all extracts met the standards, not exceeding 10%. Meanwhile, the ash content of the 80% ethanol extract did not meet the requirement as it exceeded 8.5%, while the other three extracts fulfilled the standards.